Pengaruh Disiplin Kerja dan Status Kerja terhadap Produktivitas Pemanen di PT Perkebunan Nusantara IV Afdeling 3 Kebun Dolok Ilir - Eka Andreansyah; Friska Anggraini Barus (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Harvester work productivity is a factor that determines the success of oil palm plantation companies in achieving production targets. In order to increase this productivity, an understanding of the factors that influence it is necessary, especially work discipline and employee work status. This study aims to determine and analyze the effect of work discipline and work status on harvester productivity at PT. Pembangunan Nusantara IV Afdeling 3 Kebun Dolok Ilir. The research took place from September to October 2025 with a quantitative approach. The sample determination used a simple random sampling technique involving 60 harvester employees as respondents. Research data was obtained through questionnaires, field observations, and interviews. Data analysis was carried out using validity tests, reliability tests, regression analysis equipped with hypothesis testing, including partial tests (individual), simultaneous tests (together), and coefficient of determination analysis tests were carried out with the help of SPSS 25 software. Based on the results of the study, the existence of work discipline has a significant positive impact on harvester performance, and is proven by the results of significance being less than 0.05 and the magnitude of the regression coefficient is 0.451. Meanwhile, no significant relationship was found between job status and harvester work productivity through a significance value of 0.301 > 0.05, the magnitude of the regression coefficient effect was 0.058. As a whole, work discipline and job status were proven to have a significant impact on harvester work productivity, stated through a calculated F score of 34.146 thanks to a validity level of less than 0.05. Furthermore, the magnitude of the determination coefficient (R²) reached 0.545, proven for both aspects in question can explain harvester work productivity reaching 54.5%, and the other reaching 45.5% is determined by other aspects not discussed in this study. In accordance with the results of the analysis, work discipline is the main variable that has the most influence on harvester work productivity.